1996
DOI: 10.1177/000456329603300607
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cigarette Smoking and Alcohol Consumption on Serum Liver Enzyme Activities: A Dose-Related Study in Men

Abstract: SUMMARY. The separate and joint effects of cigarette smoking and alcohol consumption on serum activities of the enzymes aspartate aminotransferase (AST), alanine aminotransferase (AL T) and y-glutamyl transferase (GGT) were investigated in 46775 men attending the BUPA Health Screening Centre in London during the period 1983-1987, after allowing for differences in age, body mass index and exercise level. As expected, all showed a significant positive correlation with alcohol consumption. Cigarette smoking produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
2
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 16 publications
8
47
2
2
Order By: Relevance
“…The rise in the AST and ALT after the nicotine is well attributed to the damage caused by systemically treated nicotine thereby inducing the release of AST and ALT from the liver. However, the multi center clinical study on chronic smokers in men in London showed no significance changes in AST or ALT activities with smoking (Whitehead et al 1996). Liver enzyme GGT is an important predictor of incidence and mortality of various diseases in particular to cardiovascular risk was not influenced by nicotine treatment in our study.…”
Section: B a D C Econtrasting
confidence: 60%
“…The rise in the AST and ALT after the nicotine is well attributed to the damage caused by systemically treated nicotine thereby inducing the release of AST and ALT from the liver. However, the multi center clinical study on chronic smokers in men in London showed no significance changes in AST or ALT activities with smoking (Whitehead et al 1996). Liver enzyme GGT is an important predictor of incidence and mortality of various diseases in particular to cardiovascular risk was not influenced by nicotine treatment in our study.…”
Section: B a D C Econtrasting
confidence: 60%
“…In a on healthy male workers ( Chan-Yeung et al, 1981). However, in the current study and similar to another report this correlation was not significant (Jang et al, 2012;Meltzer et al, 1986;Whitehead et al, 1996).…”
Section: Resultssupporting
confidence: 70%
“…However, in the study on Danish Population as well as a study based on male in London reported the raised level serum liver enzymes with self-reported alcohol consumption (Steffensen et al, 1997;Whitehead et al, 1996). This could be because the total alcohol consumption in our subjects might have been lower than in other studies.…”
Section: Resultscontrasting
confidence: 51%
“…In addition to known measures, such as avoidance of alcohol consumption and hepatotoxic drugs, a number of other variables, such as coffee consumption (23 ), weight loss (24 ), smoking cessation (25 ), and changes in nutrition (7 ), have been described to be beneficial in reduction of serum GGT. Both cutaneous and surgical revascularization are able to abolish the GGT prognostic value, confirming its link with the evolution of atherosclerotic plaque (12 ).…”
Section: Therapeutic Measures For Lowering Ggtmentioning
confidence: 99%